Student Teachers' Perception on the Implementation of Introduction to the School Field as a Provision to Teaching Profession - Irvianti, Rekha; Antosa, Zariul; Noviana, Eddy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
The purpose of this study was to determine the perceptions of the student teachers of the Elementary School Teacher Study Program (PGSD) as a provision to the teaching profession. This research is a quantitative descriptive. The population of this study were all student teachers from batch 2015 and 2016 who had participated in the introduction to the school field (PLP) program. Sampling in this study was taken using accidental techniques, seen from the number of research samples of 50 student teachers of batch 2015 and 47 student teachers of batch 2016. The data collection method used was a questionnaire. Data analysis techniques were done using quantitative data analysis of percentage formulas. Student perceptions can be seen from each indicator as follows: (1) Indicator of absorption of stimuli or objects from outside individuals from the perception of batch 2015 student teachers acquired an average percentage of 75.28% with the category of